Computed Tomographic Findings in the Nasal and Paranasal Sinuses of Patients Scheduled for Rhinoplasty at Mostafa Khomeini Hospital between 2011-13 - Abbasi, Mehdi; Alkarzae, Mohammed; Izadi, Poopak (ENT Updates, 2019)
Objective: Rhinoplasty is done to improve the morphology of the nose whilst also restoring its physiological function. Currently it is possible to perform rhinoplasty and endoscopic sinus surgery simultaneously. The need has therefore arisen to evaluate anatomical variation within the nose and paranasal sinuses in symptom-free patients who are scheduled for rhinoplasty. Coronal computed tomography (CT) is the standard method used to evaluate the nose and paranasal sinuses. We aimed to evaluate the frequency of anatomical variation noted within the nose and paranasal sinuses on coronal CT in patients scheduled for rhinoplasty. Methods: This is a descriptive, cross-sectional, retrospective study of CT findings in 84 patients who underwent rhinoplasty at Mostafa Khomeini Hospital, Shahed University, Tehran between 2011-13. The CT findings were evaluated in three different predefined categories: nasal septal, nasal turbinate, and paranasal sinuses abnormalities. Results: The study involved 84 individuals, consisting of 26 men and 58 women. The most frequent findings in the nasal septum category were nasal septal deviation (69.04%) and nasal septal spur (33.33%), whereas concha bullosa (45.23%) and inferior turbinate hypertrophy were the most frequent abnormality in the nasal turbinates category. Mucosal thickening of the sinuses (45.23%) and partial opacification of the sinuses (21.42%) were the most common findings in the paranasal sinuses. Conclusion: The high frequency of anatomical variation, inflammatory and congenital abnormal findings in CT images of the paranasal sinuses in patients scheduled for rhinoplasty indicates that preoperative CT examination may be useful in avoiding multiple surgical operations and in reducing costs.